Hybrid Incompatibilities and Transgressive Gene Expression Between Two Closely Related Subspecies of Drosophila - Go, Alwyn C.; Civetta, Alberto (Frontiers in Genetics, 2020)
Genome-wide assays of expression between species and their hybrids have identified genes that become either over or under-expressed relative to the parental species (i.e. transgressive). Transgressive expression in hybrids is of interest because it highlights possible changes in gene regulation linked to hybrid dysfunction. Previous studies in Drosophila that used long-diverged species pairs with complete or nearly complete isolation (i.e. full sterility and partial inviability of hybrids) and high-levels of genome misregulation have found correlations between expression and coding sequence divergence. The work highlighted the possible effects of directional selection driving sequence divergence and transgressive expression. Whether the same is true for taxa at early stages of divergence that have only achieved partial isolation remains untested. Here, we reanalyze previously published genome expression data and available genome sequence reads from a pair of partially isolated subspecies of Drosophila to compare expression and sequence divergence. We find a significant correlation in rates of expression and sequence evolution, but no support for directional selection driving transgressive expression in hybrids. We find that most transgressive genes in hybrids show no differential expression between parental subspecies and used SNP data to explore the role of stabilizing selection through compensatory mutations. We also examine possible misregulation through cascade effects that could be driven by interacting gene networks or co-option of off-target cis-regulatory elements.